Survey of Students’ Participation in Physical Education Learning and Athletic Materials - Suhenda, Hendrawan; Putri, Siti Ayu Risma; Lestari, Hikmah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to determine students’ interest in physical education and health subjects in athletics at SDN 01 Lahat Regency. This research uses quantitative descriptive research methods along with survey methods. Where, this research was conducted on class V students of SDN 01 Lahat Regency. The population of this study was all 35 people. The sample taken in this research was 35 people obtained using total sampling technique. Research data collection was carried out by giving questionnaires to the sample. The data analysis technique used in processing research data is data analyzed using descriptive statistical techniques in the form of mean, mode, standard deviation and coefficient of variance. The results of the study showed that 4 students (11.47%) had an interest in physical education subject matter. athleticism is in the very high category. 5 students (14.28%) had an interest in physical education subjects, athletic material, which was in the high category, 9 students (25.71%) had an interest in physical education subjects, athletic material, which was in the medium category and 17 students (48.57%) have interest in physical education subjects, athletic material, which is in the low category. And there are no students who have an interest in physical education subjects, the athletic material is in the very low category. It can be concluded that interest in physical education subjects in athletics at SDN 01 Lahat Regency is still in the low category so an analysis of the factors that influence interest in physical education subjects in athletics at SDN 01 Lahat Regency is needed and special learning methods are also needed to increase interest in physical education subjects regarding athletics at SDN 01 Lahat Regency.